2017
DOI: 10.1016/j.bbmt.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Donor CTLA-4 Genotype Modulates the Immune Response to Minor Histocompatibility Antigen Mismatches

Abstract: Minor histocompatibility antigen (miHA) mismatches have been related to graft-versus-host disease (GVHD) after allogeneic stem cell transplantation, but this association remains controversial due to the lack of consistency in the results obtained by different groups. The CTLA-4 genotype of the donor has been reported to be relevant in the appearance of acute GVHD. We explored the effect of the donor's CTLA-4 genotype in the incidence of acute GVHD associated with HA-1, HA-8, or H-Y miHA mismatches in a large c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…Autosomal MiHA mismatches increased the incidence of relapse-free survival after HLA-matched sibling transplantations (43). It was recently reported that mismatches for two HLA-A * 02:01-restricted MiHAs: HA-1 and HA-8 increased the incidence of severe acute GvHD when the donor had A/A genotype in rs231775 of CTLA4 gene (44). The contribution of mismatches of the other MiHAs to the clinical outcome has not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Autosomal MiHA mismatches increased the incidence of relapse-free survival after HLA-matched sibling transplantations (43). It was recently reported that mismatches for two HLA-A * 02:01-restricted MiHAs: HA-1 and HA-8 increased the incidence of severe acute GvHD when the donor had A/A genotype in rs231775 of CTLA4 gene (44). The contribution of mismatches of the other MiHAs to the clinical outcome has not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Анализ гомогенной когорты из 33 пациентов с острыми лейкозами после алло-ТГСК от HLA-совместимых неродственных доноров указывает на роль полиморфизма c.49A>G гена CTLA4 у донора в контроле над опухолью: для генотипа A/A полиморфизма с.49A>G 3-летняя безрецидивная выживаемость составила 12,7 % и вероятность развития рецидива -83,7 %; для генотипов A/G и G/G 3-летняя безрецидивная выживаемость -62,8 % и вероятность рецидива -29,3 %. В исследованной группе пациентов не обнаружено значимого влияния на вероятность развития и степень тяжести РТПХ, показанного в других исследованиях [15][16][17], что, возможно, объясняется используемым протоколом профилактики РТПХ, включающим антитимоцитарный глобулин. Применение антитимоцитарного глобулина снижает летальность, связанную с РТПХ, но повышает вероятность развития рецидива [18][19][20].…”
Section: Discussionunclassified
“…Также применяли метотрексат в дозе 15 мг/м 2 на +1-й и 10 мг/м 2 на +3, +6 и +11-й день соответственно. Для статистического анализа генотипы G/G и A/G соответствующих доноров были сгруппированы, поскольку в нескольких работах показана роль генотипа c.49A>G АА в развитии аллоиммунных процессов после алло-ТГСК [10,15]. Полученные группы не различались по тем факторам, которые могли бы повлиять на вероятность развития рецидива и безрецидивную выживаемость: режим кондиционирования, статус заболевания, развитие острой и хронической РТПХ.…”
Section: фундаментальные исследования в практической медицине на соврunclassified
“…A previous study demonstrated that donor CTLA-4 rs231775 genotype modulates the immune response to minor histocompatibility antigen mismatches. 46 The CTLA-4 rs231775 genotype was also considered as a genetic determinant in autoimmune Addison’s disease. 47 Recently, a number of case–control studies focused on the relationship between CTLA-4 rs231775 G>A SNP and the risk of cancer, and results of subsequent meta-analyses evidenced that the CTLA-4 rs231775 G>A polymorphism was a risk factor for multiple cancer, especially in Asian populations.…”
Section: Discussionmentioning
confidence: 99%